Reseña/Review (Mendoza, J.J., "Internet, el último continente. Mapas, e-Topias, cuerpos", Buenos Aires: La Crujía, ISBN: 978-987-4168-05-4, 94 págs., 2017) - Domínguez Cáceres, Roberto (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2018)
Reseña/Review (Mendoza, J.J., "Internet, el último continente. Mapas, e-Topias, cuerpos", Buenos Aires: La Crujía, ISBN: 978-987-4168-05-4, 94 págs., 2017)